Regulation of the major proline permease gene of Salmonella typhimurium. - Ratzkin, B (1978)
The structural gene for the major proline permease is located in a tight cluster with genes coding for the proline degradative enzymes, proline oxidase and pyrroline-5-carboxylic acid dehydrogenase. Expression of the permease is regulated in parallel with the two degradative enzymes, and all three functions are subject to catabolite repression. Regulatory mutants (putC) have constitutively high levels of all three activities, suggesting that all are regulated by a single mechanism.